Analysis Of The Factors That Influence The Growth Of Sharia Insurance Industry Assets In Indonesia (2016-2020 Period) - Suryadi, Hilman (Universitas Trunojoyo Madura, 2021)
This study aims to look at the description and influence of contributions, claims, investment returns, inflation, JCI, and BANK INDONESIA SHARIA CERTIFICATE yields on the growth of Sharia insurance industry assets in Indonesia for the 2016-2020 period, both simultaneously and partially. The data used are secondary data for the monthly period in 2016-2020. This study uses multiple linear regression analysis with the help of Eviews 10 software to see the effect of the independent variable on the dependent variable. Based on the research results, simultaneously all variables have a significant effect on asset growth. Partially, the claims variable and the JCI have a significant negative effect on asset growth, while the contribution and investment return variables have a significant positive effect on asset growth, then the inflation variable and BANK INDONESIA SHARIA CERTIFICATE yield have no significant effect on the growth of Islamic insurance industry assets in Indonesia